The Politics of Development in the Philippines - Almonte, Jose T. (Kasarinlan: Philippine Journal of Third World Studies, 2008)
Political conflicts among different social groups have produced economic stagnation, and worse, a pervasive loss of morale that has made the Philippine condition an exception to the general trend of growth and rising living standards in the world's fastest growing region. Like its vigorous neighbors, the Philippines must self-consciously learn how to compete with the world. Democratizing the economy-wresting economic control from the Filipino oligarchs-through state intervention is the key to attaining the competitiveness of the East Asian "tiger" economies.